2009
DOI: 10.1111/j.1365-2966.2009.15123.x
|View full text |Cite
|
Sign up to set email alerts
|

The ultraluminous state

Abstract: We revisit the question of the nature of ultraluminous X‐ray sources (ULXs) through a detailed investigation of their spectral shape, using the highest quality X‐ray data available in the XMM–Newton public archives (≳10 000 counts in their EPIC spectrum). We confirm that simple spectral models commonly used for the analysis and interpretation of ULXs (power‐law continuum and multicolour disc blackbody models) are inadequate in the face of such high‐quality data. Instead we find two near ubiquitous features in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

102
806
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 493 publications
(915 citation statements)
references
References 102 publications
(157 reference statements)
102
806
7
Order By: Relevance
“…Based on high-energy spectral curvature, X-1 appears to be in a super-Eddington state in its highest luminosity observations, as has been suggested by previous authors (Watarai et al 2001;Ebisawa et al 2003;Feng & Kaaret 2009;Yoshida et al 2012). This spectral curvature has been theorized to be the result of heavy Comptonization by a cool, optically thick corona when the source is in a high accretion state (Gladstone et al 2009). However, at low luminosity X-1 appears to transition to a sub or near-Eddington accretion state where high energy curvature is less significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on high-energy spectral curvature, X-1 appears to be in a super-Eddington state in its highest luminosity observations, as has been suggested by previous authors (Watarai et al 2001;Ebisawa et al 2003;Feng & Kaaret 2009;Yoshida et al 2012). This spectral curvature has been theorized to be the result of heavy Comptonization by a cool, optically thick corona when the source is in a high accretion state (Gladstone et al 2009). However, at low luminosity X-1 appears to transition to a sub or near-Eddington accretion state where high energy curvature is less significant.…”
Section: Discussionmentioning
confidence: 99%
“…Spectral curvature above ∼6 keV in the hard component of a large fraction of ULX spectra (Stobbart et al 2006;Gladstone et al 2009;Miyawaki et al 2009) distinguishes them from BHBs, whose hard component is generally modelled by a powerlaw which extends unbroken to much higher energies, often above ∼100 keV. With sensitivity above 10 keV, recent observations with the Nuclear Spectroscopic Telescope Array (NuStar ) have confirmed a spectral cutoff in ULXs such as NGC 1313 X-1 (Bachetti et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…sources in the original ultraluminous state description of ULX accretion, as suggested by Gladstone et al (2009). In this scenario, the two components in the X-ray spectrum correspond to emission from a soft truncated disc and a hard corona.…”
Section: A N E W S P E C T R a L M O D E L O F A N I R R A D I At E Dmentioning
confidence: 99%
“…They use this to calculate a mass function, and find that it likely contains an ∼20-30 M black hole. Gladstone, Roberts & Done (2009) identified three types of ULX X-ray spectra, which they suggested may represent a spectral sequence with increasing accretion rate. They suggested that around the Eddington limit ULXs appear with broad disc-like X-ray spectra, whilst at higher accretion rates a two-component X-ray spectrum emerges.…”
Section: Introductionmentioning
confidence: 99%
“…Recent deep optical spectroscopy revealed that the broad emission lines of H and He observed in ULXs (and also SS 433, which is the only known Galactic X-ray binary thought to power persistent supercritical accretion; see Fabrika 2004 and references therein) likely originate in dense, strong winds launched on supercritical accretion disks (Fabrika et al 2015). 7 Moreover, Gladstone et al (2009) suggest that massive optically thick winds could be the origin of the soft Comptonization component usually detected in ULXs. This component has a low temperature (≈3 keV) and a large optical depth (t » 5-30), similar to those estimated for the thermal Comptonization component in GRO J1655−40.…”
Section: Implications For Disk Winds In Other Luminous X-ray Binariesmentioning
confidence: 99%